2021
DOI: 10.1371/journal.pmed.1003498
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk scores in cardiovascular risk prediction: A cohort study and modelling analyses

Abstract: Background Polygenic risk scores (PRSs) can stratify populations into cardiovascular disease (CVD) risk groups. We aimed to quantify the potential advantage of adding information on PRSs to conventional risk factors in the primary prevention of CVD. Methods and findings Using data from UK Biobank on 306,654 individuals without a history of CVD and not on lipid-lowering treatments (mean age [SD]: 56.0 [8.0] years; females: 57%; median follow-up: 8.1 years), we calculated measures of risk discrimination and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 40 publications
6
105
0
Order By: Relevance
“…Polygenic scores (PGSs) for CAD have been shown to have predictive value over risk scores based on clinical factors alone 10,11,42,[50][51][52][53][54] . To assess the transferability of PGSs for cardiometabolic traits derived from EUR populations into BPB individuals, we compared predictive performance in G&H to that in EUR individuals from eMERGE.…”
Section: Variable Transferability Of Polygenic Scoresmentioning
confidence: 99%
See 2 more Smart Citations
“…Polygenic scores (PGSs) for CAD have been shown to have predictive value over risk scores based on clinical factors alone 10,11,42,[50][51][52][53][54] . To assess the transferability of PGSs for cardiometabolic traits derived from EUR populations into BPB individuals, we compared predictive performance in G&H to that in EUR individuals from eMERGE.…”
Section: Variable Transferability Of Polygenic Scoresmentioning
confidence: 99%
“…Previous studies in UKBB EUR samples reported similar improvement, with NRI estimates of 3.5% (95% CI: 2.4-4.5%) 10 and 3.7% (95% CI: 3.0-4.4%) 9 in two different analyses using CAD as the outcome. However, these NRI estimates are probably inflated by using UKBB samples that are healthier than the general UK population without recalibrating risk to a primary care setting 11 . In G&H, the PGS improved identification of high-risk individuals in people younger than 55 years, and correctly downclassified low-risk individuals in people older than 55 years, both of which are important in a clinical setting.…”
Section: Based On Findings In Lipid Traits the Global Lipids Genetics Consortium Recently Claimed Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…There is significant additive value of integrating genome-wide genetic data to enhance risk prediction using polygenic scores (PGS) (7-9(10)). Additionally, individuals with a PGS in the highest 8% of score distribution have a risk of CAD comparable to having monogenic familial hypercholesterolemia (3-fold increased risk) (10). To date, investigators have shown that adding PGS (11)(12)(13)(14)(15)(16)(17) to standard risk prediction algorithms enhances the power of the model to predict CAD, consistent with the estimated contribution of genetic factors responsible for 40-50% of CAD risk (18).…”
Section: Introductionmentioning
confidence: 73%
“…Similarly, augmenting PRS with additional information such as BMI, and lab results such as HDL and LDL measures improved prediction power for T2D [ 37 ]. Similarly, augmenting PRS by traditional measures for cardiovascular disease risk modestly enhanced its prediction power [ 38 ]. In addition, a recent study added mortality risk factors to disease PRS to mark individuals with higher mortality risk [ 39 ].…”
Section: Discussionmentioning
confidence: 99%